Pulse-duration dependence of the double-to-single ionization ratio of Ne by intense 780-nm and 800-nm laser fields: Comparison of simulations with experiments - Chen, Zhangjin; Zhang, Lina; Wang, Yali; Zatsarinny, Oleg; Bartschat, Klaus; Morishita, Toru; Lin, C. D. (My University, 2019)
Accurate ab initio calculations of the ratio of double-to-single ionization of Ne atoms in strong laser fields are difficult due to the many-electron nature of the target. Here, with accurate total cross sections carefully evaluated by using the state-of-the-art many-electron R-matrix theory for both electron-impact ionization and electron-impact excitation of Ne+, we simulate the total double-ionization yields of Ne2+ in strong laser fields at 780 and 800 nm for pulse durations in the range from 7.5 to 200 fs based on the improved quantitative rescattering model. The corresponding single-ionization yields of Ne+ are calculated within the nonadiabatic tunneling model of Perelomov, Popov, and Terent'ev. The ratio of double-to-single ionization of Ne is then obtained from the calculated double- and single-ionization yields. By normalizing the ratio to the one calculated from solving the time-dependent Schrödinger equation for a short few-cycle pulse, we make quantitative comparisons of our results with experimental data to show that our model predicts the experimental findings very well. Finally, we analyze the pulse-duration dependence of the double-to-single ionization ratio.
Keywords: ionization ration; pulse-duration; double-to-single ionization